(untitled) (The Journal of Ad-din Women’s Medical College, 2025)
Background: A ruptured uterus is a catastrophic condition. It is associated with a high incidence of fetal and maternal mortality and morbidity. Objective: To determine the incidence, risk factors, maternal and fetal outcome, and management of uterine rupture in Ad-din Women’s Medical College and Hospital, Dhaka, Bangladesh. Materials and Methods: This prospective observational study of patients with ruptured uterus from July 2022 to June 2023 admitted at Gynaecology and Obstetrics department of Ad-din Women’s Medical College and Hospital, Dhaka. All the cases of ruptured uterus who were either admitted with ruptured uterus or who developed it in hospital were included in the study. Patients were initially assessed in emergency and labor wards, and relevant sociodemographic data, obstetric history, and previous antenatal and surgical history were recorded. Ways of management, and maternal and fetal outcomes were taken for analysis. Results: There were 45 cases of ruptured uterus out of a total of 17,288 deliveries over one year with a prevalence of 0.26%. The most common age group was 30-35 years, and most of the patients 37(82.2%) had a history of previous cesarean section. A maximum of 24 (53.3%) rupture of the uterus was found >36-40 weeks. Subtotal hysterectomy was done in 4 (8.9%) patients, and Subtotal hysterectomy with the repair of the bladder was done in 2 (4.4%) patients, out of 45 patients, 4 (8.9%) patients developed acute renal failure and maternal death was found 4 (8.9%) patients. IUFD was found in 21 (46.7%) babies, 10 (22.2%) babies needed NICU and neonatal death was found in 4 (8.9%) babies. Conclusion: Uterine rupture is a preventable obstetric complication that carries severe risks both to the mother and to the baby. Proper antenatal care, appropriate counseling of patients with a history of previous caesarian section for hospital delivery, and training of skilled birth attendants can reduce maternal and perinatal mortality and morbidity due to ruptured uterus. The Journal of Ad-din Women’s Medical College; Vol. 12 (2), July 2024; p 5-10